The Influence of Profitability, Taxes, and Foreign Ownership on Transfer Pricing (An Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange from 2015-2021) - Dianty Putri Purba; Doanrikus Manalu; Sinta Friska Br Ketaren; Pebriyanti Tampubolon (Kusuma Negara Business School, 2023)
The main point of this study is that transfer pricing, which is used by multinational companies to settle prices and transactions between divisions, allows businesses to reduce internal prices for commodities, services, and unwanted or excessive assets. The purpose of transfer pricing is to manage transfer prices between businesses with the specific goal of increasing the total tax liability within the company. The study population consisted of 143 manufacturing companies listed on the Indonesia Stock Exchange (BEI) between 2015 and 2021. For the quantitative research type, 15 companies were selected using purposive sampling as the research sample. The information used was secondary data, namely the companies' financial records obtained from www.idx.co.id. Descriptive statistics, classical assumption tests, multiple regression analysis, outliers, F-statistics tests, and F-statistics tests were the data analysis techniques used. Transfer Price, the dependent variable of the study, was represented by RTP (Related Party Transaction). Profitability, Taxes, and Foreign Ownership were the independent variables used. Multiple regression analysis using SPSS 20 was the analytical approach employed in this research. According to the findings of this study, Profitability, Taxes, and Foreign Ownership do not simultaneously impact Transfer Pricing. The findings in this research explain that foreign ownership and taxes do not influence transfer pricing, nor do profits or taxes have any relationship with transfer pricing.